Football - Flinders, Steve (Oxford University Press, 1996)
Factfiles are a sub-series of "Bookworms" with a non-fiction angle, providing factual information for students who are less interested in fiction. Each book focuses on a particular topic such as famous cities, sport, science, the environment and the media